Is Slow Productivity and Output Growth in Advanced Economies the New Normal? - John Fernald (International Productivity Monitor, 2018)
Advanced economies have seen a notable slowdown in potential growth in the past decade or so. Demographics look much less favorable to output growth than in the past, and productivity growth has been only modest. The demographic and productivity factors driving this slowdown in potential growth look to be largely independent of the Great Recession. These factors do not at this point look likely to change rapidly, despite considerable uncertainty about the future contribution of artificial intelligence and robots.